Une methode simplifiee pour l’analyse du delaminage aupres d’un bord droit - Daudeville, Laurent; Ladeveze, Pierre (European Journal of Computational Mechanics, 1994)
A simplified method based upon damage mechanics for the delamination analysis of composites is presented. In the neighbourhood of a quasi-straight edge of a laminated structure, damage is taken concentrated on the interface between layers. The finite element code EDA, acting as a post-processor of an elastic laminate shell computation, allows the prediction of delamination onset and propagation. Numerical simulations of delamination are given and compared with experimental results from literature.